A STUDY TO EXAMINE HOW AI AND ML AFFECT IT STRATEGIC PLANNING AND LONG-TERM ORGANIZATIONAL OBJECTIVES - Bhuvan, Seema (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper explores how Artificial Intelligence (AI) and Machine Learning (ML) influence IT strategic planning and long-term organizational objectives. As businesses increasingly rely on data-driven insights and automation, AI and ML technologies are transforming IT strategies. These technologies enable organizations to streamline operations, enhance decision-making, and maintain competitive advantages in an ever-evolving market. This research examines the integration of AI and ML into IT strategy, its impact on organizational goals, and the challenges and benefits these technologies present. It also discusses the potential threats, key findings, and how organizations can align AI and ML with their long-term strategies.